(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
This article examines the problems of hygienic assessment of working conditions of medical personnel in physiotherapy rooms involved in physiotherapy procedures for the purpose of rehabilitation of various population groups. The dynamics of the performance of medical workers during the working day and working week were studied. An assessment was made of the working conditions based on the indicators of harmfulness and danger of factors of the working environment of workers, the severity and intensity of the work process. Thus, the working conditions of medical personnel according to SanPiN RUz No. 0141-03 "Hygienic classification of working conditions based on indicators of harmfulness and danger of factors of the working environment, the severity and intensity of the work process" are classified as "harmful" class 3, 1-2 degrees